Very low birth weight newborn with diabetes mellitus due to pancreas agenesis managed with insulin pump reservoir filled with undiluted insulin: 16-month follow-up. Issue 7 (July 2022) - Zanfardino, Angela; Piscopo, Alessia; Curto, Stefano; Schiaffini, Riccardo; Rollato, Assunta S.; Testa, Veronica; Miraglia del Giudice, Emanuele; Barbetti, Fabrizio; Iafusco, Dario
Abstract: Background: When very low doses of insulin are used insulin dilution, a procedure prone to errors, is recommended. Case presentation: We managed a neonate with pancreas agenesis with insulin pump therapy from the first days of life to 16 months of age without insulin dilution. Predictive low glucose suspend mode first and then closed loop control were used. No episodes of severe hypoglycemia were observed. Conclusions: Though limited to a single patient with pancreas agenesis we believe that the use of pump should be warranted in patients with permanent neonatal diabetes mellitus and intestinal malabsorption, even with undiluted insulin.